Development and evaluation of a new lateral flow assay for simultaneous detection of antibodies against African horse sickness and equine infectious anemia viruses - Costa, Sofia (2016)
African horse sickness (AHS) and equine infectious anemia (EIA) are both notifiable equid specific diseases that may present similar clinical signs. Considering the increased global movement of horses and equine products over the past decades, together with the socio-economic impact of previous AHS and EIA outbreaks, there is a clear demand for an early discrimination and a strict control of their transmission between enzootic and AHS/EIA-free regions. Currently, the individual control and prevention of AHS or EIA relies on a series of measures, including the restriction of animal movements, vector control, and the use of several laboratory techniques for viral identification, amongst others. Despite being widely employed in surveillance programmes and in the control of animal movements, the available serological assays can only detect AHS- or EIA-specific antibodies individually. In this work, a duplex lateral flow assay (LFA) for simultaneous detection and differentiation of specific antibodies against AHS virus (AHSV) and EIA virus (EIAV) was developed and evaluated with experimental and field serum samples. The duplex LFA was based on the AHSV-VP7 outer core protein and the EIAV-P26 major core protein. The results indicated that the duplex LFA presented a good analytical performance, detecting simultaneously and specifically antibodies against AHSV and EIAV. The initial diagnostic evaluation revealed a good agreement with results from the AHS and EIA tests prescribed by the OIE, and it highlighted the usefulness of the new AHSV/EIAV duplex LFA for an on-field and point-of-care first diagnosis.